THEMATIC HORIZONS OF POUBLITSISTICI OF VLADIMIR BIRCHACAK(ON MATERIALS OF NEWSPAPER THE "UKRAINIAN WORD") - Novac, S. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
For the first time in the Ukrainian literary criticism on the material of newspaper “Ukrajins’ke slovo” thematic horizons and ideological orientation of V.Birchak’s publicism of 20 – 40ies of XXth century has been stadied.